2015
DOI: 10.1371/journal.pone.0129531
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastasis, a Unique Independent Prognostic Factor in Early Gastric Cancer

Abstract: BackgroundLymph node metastasis (LNM) has been shown to be related to the prognosis of early gastric cancer (EGC). The choice of optimal treatment depends on an accurate pre-operative assessment of LNM status in EGC patients. However, in China, where EGC cases account for only a small part of gastric cancer (GC) cases, there are not enough data to make an accurate assessment. Therefore, this study, which involved a relatively large number of EGC patients, aimed to explore the relationship between clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 20 publications
6
42
1
Order By: Relevance
“…Unexpectedly, endoscopic ulcerated pattern was not identified as a risk factor for LNM in this cohort. According to Japanese investigators, ulcerated EGC are associated with an increased risk of LNM, which was not verified in our cohort and most other Chinese cohorts . We showed that ulcerated EGC tumors were primarily found in the DGC group with no increased LNM risk.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Unexpectedly, endoscopic ulcerated pattern was not identified as a risk factor for LNM in this cohort. According to Japanese investigators, ulcerated EGC are associated with an increased risk of LNM, which was not verified in our cohort and most other Chinese cohorts . We showed that ulcerated EGC tumors were primarily found in the DGC group with no increased LNM risk.…”
Section: Discussioncontrasting
confidence: 93%
“…The standard criteria for endoscopic resection of EGC, according to the Japanese Gastric Cancer Association (JGCA) guidelines, include tumors with mucosal or submucosal invasion up to 500 µm (SM1), size up to 2 cm for EMR and 3 cm for ESD, having a non‐excavated gross pattern and a differentiated histological type (i.e., tubular and papillary adenocarcinomas of the Lauren classification). Although widely adopted, the application of the JGCA guidelines in the management of EGC in Chinese patients has been questioned by many Chinese studies that have identified different independent risk factors such as male sex, tumor size ≥2 cm and depth of tumor invasion. Several Chinese studies also reported the recurrence rates of up to 12.2% and LNM rates up to 25.4% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulceration was again confirmed as a non‐risk factor of LNM in this large multicenter study. Overall, these results are parallel to those reported previously and add to the growing body of knowledge by providing more precise features of LNM in EGC of Chinese patients . The findings may help to improve the decision‐making process for managing Chinese patients with EGC.…”
Section: Discussionsupporting
confidence: 85%
“…While lymphovascular invasion has been confirmed worldwide as the most important risk factor for nodal metastasis in EGC [19,46,47], an extremely low frequency of nodal metastasis in EGC for intramucosal carcinoma, tumor size smaller than 2 cm, and superficial submucosal invasion without lymphovascular invasion, reported previously [43], has not been universally confirmed (Table 2). Several recent Chinese and Korean studies on nodal metastasis in EGC also demonstrate different risk factors such as female gender [18,19,48], intestinal type [47], and distal gastric location [18,49,50], but not ulceration [18,49,51]. A most recent systematic review of the world literature in 42 qualified studies shows low, but substantial, nodal metastasis rates of 6% for intramucosal carcinoma, 9% for EGC without lymphovascular invasion, 13% for the intestinal-type EGC, 13% for EGC with an elevated growth pattern, and 8% for EGC in the size smaller than 2 cm [47].…”
Section: Unsettled Risk Factors Of Lymph Node Metastasismentioning
confidence: 99%